Answer :

Answer:

Can I get brainliest please?

Step-by-step explanation:

Ok so, Let's solve your equation step-by-step.

5x−2(2x−1)=6

Step 1: Simplify both sides of the equation.

5x−2(2x−1)=6

5x+(−2)(2x)+(−2)(−1)=6(Distribute)

5x+−4x+2=6

(5x+−4x)+(2)=6(Combine Like Terms)

x+2=6

x+2=6

Step 2: Subtract 2 from both sides.

x+2−2=6−2

x=4

So, your answer would be:

x=4

cbh6

Answer:

x=4

Step-by-step explanation:

5x-2(2x-1)=6

multiply 2 to the parathesis

5x-4x+2=6

collect like terms

x+2=6

subtract both sides by 2

x=4

Other Questions